Different types of vascularized free fibula flaps for the reconstruction of mandibular defects：A retrospective analysis - SONG Lina; WU Chunyue; QIN Qingyan; CHU Tianshu; LIU Qilin (Kouqiang hemian waike zazhi)
[Objective] To evaluate the diversity and flexibility of vascularized free fibular flap (FFF) for soft and hard tissue defects of the lower third of face and oromandibular reconstruction. [Methods] We collected 35 patients who underwent segmental resection of the mandible due to benign or malignant tumors and reconstructed with vascularized FFF. The types of mandibular defects, preoperative design, methods of FFF reconstruction and categories of skin islands were analyzed. [Results] According to the COM classification, there were 6 cases of type Ⅰ, 26 cases of type Ⅱ and 3 cases of type Ⅲ. The length of the mandibular defects ranged from 4.85 cm to 17.00 cm, with an average of (8.29±2.69) cm. Among them, 28 cases were reconstructed with vascularized FFF, in which the width of the monolayer fibula was 2.16 cm in one case; 6 cases were rebuilt with folded vascularized FFF; 1 case was restored with monolayer vascularized FFF plus non‐vascularized free fibula. Therefore, totally 8 cases perfectly restored the height of the mandible. In terms of skin islands, 1 case had no skin island due to the absence of peroneal perforator, 30 cases carried 1 skin island, 4 cases carried double skin islands, the soft tissue defects were well restored. [Conclusion] The vascularized FFF has the advantage of flexibility. In addition to restoring the continuity of the mandible, it can rebuild the height of the mandible through a variety of ways. Besides, it can also carry double skin islands to repair complex soft tissue defects.